Linking Attractions, Amenities, and Tourist Satisfaction: A Conceptual and Empirical Study of Pasir Padi Beach, Indonesia - Laia, Patrisia; Listyorini, Haniek (Politeknik Negeri Bandung, 2025)
Coastal destinations often emphasize natural attractions but overlook the role of supporting amenities in shaping tourist comfort and satisfaction. Existing research on Indonesian beach tourism remains largely descriptive, rarely integrating these dimensions within a conceptual framework. This study investigates how the development of attractions and amenities contributes to tourist comfort and satisfaction at Pasir Padi Beach, Pangkalpinang. Using a qualitative approach through semi-structured interviews, field observations, and document analysis, the data were thematically analyzed and triangulated across stakeholder perspectives. Findings reveal that while the beach offers distinctive natural and event-based attractions, limited and poorly maintained amenities—such as sanitation, lighting, and spatial organization—reduce perceived comfort and satisfaction. The study develops an analytical model linking attractions–amenities–comfort–satisfaction adapted from the 4A and SERVQUAL frameworks, highlighting the interdependence between physical infrastructure and experiential quality. Theoretically, the research contributes to destination development discourse by contextualizing service quality concepts in coastal settings; practically, it provides guidance for local governments in integrating amenity improvement within sustainable tourism planning.